Alachlor Use and Cancer Incidence in the Agricultural Health Study: An Updated Analysis. (17th February 2018) - Lerro, Catherine C; Andreotti, Gabriella; Koutros, Stella; Lee, Won Jin; Hofmann, Jonathan N; Sandler, Dale P; Parks, Christine G; Blair, Aaron; Lubin, Jay H; Beane Freeman, Laura E
Abstract: Background: The herbicide alachlor has been widely used in US agriculture since its introduction in 1969. Experimental animal studies show that alachlor causes tumors in vivo; however, few epidemiologic studies have examined associations with human cancer risk. We evaluated alachlor use and cancer incidence in the Agricultural Health Study, updating an earlier analysis that suggested associations with lymphohematopoietic cancers with an additional 540 142 person-years of follow-up and 5113 cancer cases. Methods: Pesticide applicators in Iowa and North Carolina reported lifetime alachlor use at enrollment (1993–1997) and follow-up (1999–2005). Exposure was characterized by cumulative intensity-weighted days. We estimated relative risks (RRs) and 95% confidence intervals (CIs) using Poisson regression for incident cancers from enrollment through 2012(NC)/2013(IA). Models adjusted for age, tobacco, alcohol, and other pesticides. All statistical tests are two-sided. Results: Among 49 685 applicators, 25 640 (51.6%) used alachlor, with 3534 alachlor-exposed cancers. The relative risks of laryngeal cancer (nexposed = 34) increased in the second (RR = 4.68, 95% CI = 1.95 to 11.23), third (RR = 6.04, 95% CI = 2.44 to 14.99), and fourth quartiles (RR = 7.10, 95% CI = 2.58 to 19.53) of intensity-weighted days of use compared with no use ( P trend = .001). Risk of myeloid leukemia was elevated, though not statistically significantly so, in the fourth quartile of intensity-weighted days of use (RR = 1.82, 95% CI = 0.85 to 3.87, P trend = .17). Conclusions: We observed a strong positive association with use of alachlor and laryngeal cancer and a weaker association with myeloid leukemia. The strength and robustness of the association with laryngeal cancer suggests that long-term occupational exposure to alachlor may be a risk factor for laryngeal cancer. This first report requires confirmation.